Prolonged exposure to heat enhances mosquito tolerance to viral infection - Hugo D. Perdomo; Ayda Khorramnejad; Nfamara M. Cham; Alida Kropf; Davide Sogliani; Mariangela Bonizzoni (Communications Biology)
Abstract How and to what extent mosquito-virus interaction is influenced by climate change is a complex question of ecological and epidemiological relevance. We worked at the intersection between thermal biology and vector immunology and studied shifts in tolerance and resistance to the cell fusing agent virus (CFAV), a prominent component of the mosquito virome known to contribute to shaping mosquito vector competence, in warm-acclimated and warm-evolved Aedes albopictus mosquitoes. We show that the length of the thermal challenge influences the outcome of the infection with warm-evolved mosquitoes being more tolerant to CFAV infection, while warm-acclimated mosquitoes being more resistant and suffering from extensive fitness costs. These results highlight the importance of considering fluctuations in vector immunity in relation to the length of a thermal challenge to understand natural variation in vector response to viruses and frame realistic transmission models.